IFRS CONVERGENCE: A LITERATURE REVIEW - Juli Riyanto Tri Wijaya; Christina Tri Setyorini (Proceeding International Seminar of Islamic Studies, 2022)
Many countries have adopted frameworks such as IFRS (International Financial Reporting Standard) and GAAP (Generally Accepted Accounting Principles). IFRS is a more widely used accounting standard than GAAP in many countries. The various types of impacts that exist in the convergence are one of the discussed issues in adopting IFRS. This study attempts to examine some of the consequences of the adoption of these accounting standards. This literature review draws on research findings that have been cited by numerous other researchers. The researcher used the Publish and Perish version 7 software to determine which articles were used in this literature review. Another criterion used to determine the study's source is that the article be indexed by Google Scholar. According to the study's findings, the convergence of IFRS in various countries has a variety of consequences. The application of Financial Accounting Standards in Indonesia, which are convergent with IFRS, has a positive side effect, particularly for stakeholders. One of these positive effects is the ability to positively and significantly influence voluntary disclosure while reducing the potential for earnings management.Keywords:Convergence, IFRS, Accounting Standards